The Relevance of Customer Reviews in the Mobile Application Marketplaces - Sami Hyrynsalmi; Arho Suominen; Marko Seppänen; Tuomas Mäkilä (My University, 2025)
<p style="margin: 0px; padding: 0px 0px 1em; color: #202020; font-family: Verdana; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 21.59375px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">The effect of user generated product ratings has been studied by academics in different contexts from books to movies and its importance has been noted by the industry. In this study, the relevance of customer ratings in a mobile application ecosystem with two different datasets, over 174,000 applications, gathered from Google Play in December 2011 and in November 2012 is analyzed. The results show that a high average rating correlates positively with sales improvement as well as a high variance correlates positively with the number of installations, both statistically significant. The correlations are, however, small. On contrary to the suggestions of previous studies, the price of the application does not seem to affect the importance of product ratings. Further research would investigate how application providers’ brands and visibility in social media may influence on the popularity and its growth in mobile application ecosystems.
Proceedings of the 22nd International Conference on Management of Technology